An innovative navigation and guidance system for small unmanned aircraft using low-cost sensors. Issue 6 (5th October 2015) - Renuganth Varatharajoo, Prof; Sabatini, Roberto; Cappello, Francesco; Ramasamy, Subramanian; Gardi, Alessandro; Clothier, Reece
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to design a compact, light and relatively inexpensive navigation and guidance system capable of providing the required navigation performance (RNP) in all phases of flight of small unmanned aircrafts (UA), with a special focus on precision approach and landing. Design/methodology/approach – Two multi-sensor architectures for navigation and guidance of small UA are proposed and compared in this paper. These architectures are based, respectively, on a standard extended Kalman filter (EKF) approach and a more advanced unscented Kalman filter (UKF) approach for data fusion of global navigation satellite systems (GNSS), micro-electro-mechanical system (MEMS)-based inertial measurement unit (IMU) and vision-based navigation (VBN) sensors. Findings – The EKF-based VBN-IMU-GNSS-aircraft dynamics model (ADM) (VIGA) system and the UKF-based system (VIGA+) performances are compared in a small UA integration scheme (i.e. AEROSONDE UA platform) exploring a representative cross-section of this UA operational flight envelope, including high-dynamics manoeuvres and CAT-I to CAT-III precision approach tasks. The comparison shows that the position and attitude accuracy of the proposed VIGA and VIGA+ systems are compatible with the RNP specified in the various UA flight profiles, including precision approach down to CAT-II. Originality/value – The novelty aspect is the augmentation by ADM in both architectures to compensate for the MEMS-IMU sensor shortcomings in high-dynamics attitude determination tasks. Additionally, the ADM measurements are pre-filtered by an UKF with the purpose of increasing the ADM attitude solution stability time in the UKF-based system.